PROBLEMATIKA ORANG TUA SINGLE PARENT DALAM MEMBERIKAN PEMBINAAN KEAGAMAAN DI LINGKUNGAN KELUARGA: (Studi Kasus Dusun Buluh Enggadang Desa Serumpun Buluh Kecamatan Tebas Kabupaten Sambas) - Mastika; Henny Yusnita; Enik Sartika (Jurnal Ilmiah Al-Muttaqin, 2021)
The purpose of this study was to determine the problems of single parent parents in providing religious guidance in the family environment. This study uses a descriptive approach with qualitative research types. The result shows that the single parent problem in providing religious guidance to families in Buluh Engadang village has three problems, namely economic problems, social problems and educational problems. The problem experienced by single parents who are single parents is an economic problem. With this economic problem, single parent parents have spent a lot of time making a living. Single parent social problems studied have different social sides. This difference is motivated by the environment around where single parent parents live. The community considers a single parent with one eye so that people do not believe that single parent parents are unable to raise their children and educate their children, but the reality is that single parent parents are able to send their children to the university level. The problem of single parent education has different levels of education, so that single parent parents realize that education is so important.